2010
DOI: 10.1158/0008-5472.can-09-2533
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine and Angiogenic Factor Profiling Identifies Markers Associated with Tumor Shrinkage in Early-Stage Non–Small Cell Lung Cancer Patients Treated with Pazopanib

Abstract: There is an unmet need for pharmacodynamic and predictive biomarkers for antiangiogenic agents. Recent studies have shown that soluble vascular endothelial growth factor receptor 2 (sVEGFR2), VEGF, and several other soluble factors may be modulated by VEGF pathway inhibitors. We conducted a broad profiling of cytokine and angiogenic factors (CAF) to investigate the relationship between baseline CAF levels, CAF changes during treatment, and tumor shrinkage in early-stage non–small cell lung cancer (NSCLC) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 47 publications
0
78
1
2
Order By: Relevance
“…However recent data may allow reconsidering this cytokine as a therapeutic tool in selected tumor subsets. Actually it has been reported that the in vivo tumor response to IL-12 is influenced by the molecular features of its receptor [63] and that IL-12 could be a candidate for tumor shrinkage observed during the treatment of early-stage non-small cell lung cancer with tyrosine kinase inhibitors (vandetanib, pazopanib) targeting angiogenic receptors [64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…However recent data may allow reconsidering this cytokine as a therapeutic tool in selected tumor subsets. Actually it has been reported that the in vivo tumor response to IL-12 is influenced by the molecular features of its receptor [63] and that IL-12 could be a candidate for tumor shrinkage observed during the treatment of early-stage non-small cell lung cancer with tyrosine kinase inhibitors (vandetanib, pazopanib) targeting angiogenic receptors [64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, knowledge about molecular mechanisms and cellular transformation in association with cancer behavior has increased [17][18][19] . More interest has been generated since the development of specific targeted therapies against the processes involved in the carcinogenesis of many types of cancers [20][21][22] .…”
Section: Molecular Pathway Modelmentioning
confidence: 99%
“…Other report using pre-clinical studies suggested that VEGF-A www.intechopen.com induced removal or shedding of VEGFR-2 in EC. VEGFR-2 shedding resulted in tumor shrinkage in NSCLC patients that was associated with expression of ADAM metalloprotease and IL-4 (Nikolinakos et al 2010). Taken together, these results suggest that VEGFR-2 is not only a mediator of angiogenesis but a viable target.…”
Section: Lung Cancermentioning
confidence: 76%
“…This supports the theory that anti-cancer drugs targeting the VEGF pathway are possible therapeutic means. The VEGF pathway has also recently been identified as a viable therapeutic target in NSCLC (Nikolinakos et al 2010). A study utilizing a mouse model to determine if initiation and maintenance of tumor angiogenesis in NSCLC could be associated with endothelial progenitor cells (EPCs CD133+) it was found these cells express high levels of VEGFR-2.…”
Section: Lung Cancermentioning
confidence: 99%